Clinical case of the coronavirus infection in anamnesis with complication - Svitlana Mishura; Nataliia Turchyna; Yuliia Heletiuk (Bogomolets National Medical University, 2022)
coronavirus infection, the causative agent of which is SARS-CoV-2, can cause a wide range of clinical manifestations. This infection is especially dangerous for patients with a predisposition to cardiovascular diseases, such as hypertension. Changes in vascular tone under conditions of increased blood pressure, as well as dysfunction of vascular walls under the influence of a viral infection, lead to irritation of the suprasegmental part of the autonomic nervous system, namely the posterior part of the hypothalamus, which provokes the development of sympathoadrenal attacks with panic attacks. This study aimed to demonstrate that comorbid disease of the cardiovascular system occurred after coronavirus infection worsens the course of the initial manifestations of cerebrovascular insufficiency. Patient T., who suffered from COVID-19 in October 2020, was examined in the neurological department of the State Institution «Head medical center of the Ministry of Internal Affairs of Ukraine» in December-January 2020-2021. During the examination of the patient's neurological status, positive pathological reflexes were found: proboscis and Marinescu-Radovichi reflex, foot pathological Strumpell extensor reflex on both sides, and lability of the autonomic nervous system in the form of acrohyperthermia, tremors of the eyelids and fingers of outstretched hands, slight unsteadiness in the Romberg pose. The patient underwent a general blood count, biochemical blood test, Doppler ultrasound of the main arteries of the head, ultrasound of the heart, and electrocardiography (ECG). Special attention should be paid to the results of the Doppler ultrasound of the main arteries of the head: the intima-media complex thickness of the left common carotid artery in the middle third is up to 0.91 mm, in the bifurcation it has a local thickening up to 1.27 mm, the right common carotid artery in the middle third is up to 0.85 mm (normal up to 1.0 mm), in the bifurcation up to 1.04 mm (normal up to 1.1 mm), with partially lost differentiation into layers, echogenicity is not changed. In consequence of the patient's treatment with statin drugs, scavenger-receptors of monocytes are blocked, the number of which on the surface of cells is stimulated by viruses in the presence of infection, and right to them LDL are attached. Blocking of the capture of LDL by phagocytes limits the formation of foam cells, which are the basis of atherosclerotic plaques, and leads to a decrease in the intima-media complex thickness. According to the results of the ultrasound of the main arteries of the head, after six months of treatment, the thickness of the intima-media complex of the left common carotid artery decreased from 0.91 mm to 0.76 mm, the right one - from 0.85 to 0.65 mm. Conclusions. Comorbid diseases occurring under the influence of coronavirus infection, namely arterial hypertension, worsen the course of such slowly progressive disorders of cerebral blood circulation, as the initial manifestations of cerebral blood circulation insufficiency with the development of sympathoadrenal paroxysms with panic attacks. Treatment with statins, anticoagulants, antihypertensive, nootropic, and sedative drugs helps to stabilize arterial hypertension and reduce the number of sympathoadrenal attacks with panic attacks in patients.